Optically activated and interrogated plasmonic hydrogels for applications in wound healing. Issue 9 (25th June 2020) - Milanesi, Alessio; Magni, Giada; Centi, Sonia; Schifino, Gioacchino; Aluigi, Annalisa; Khlebtsov, Boris N.; Cavigli, Lucia; Barucci, Andrea; Khlebtsov, Nikolai G.; Ratto, Fulvio; Rossi, Francesca; Pini, Roberto
Abstract: We disclose the use of hybrid materials featuring Au/Ag core/shell nanorods in porous chitosan/polyvinyl alcohol scaffolds for applications in tissue engineering and wound healing. The combination of Au and Ag in a single construct provides synergistic opportunities for optical activation of functions as near infrared laser tissue bonding, and remote interrogation to return parameters of prognostic relevance in wound healing monitoring. In particular, the bimetallic component ensures optical tunability, enhanced shelf life and photothermal stability, serves as a reservoir of germicidal silver cations, and changes in near‐infrared and visible color according to the environmental level of oxidative stress. At the same time, the polymeric blend is ideal to bind connective tissue upon photothermal activation, and to support fabrication processes that provide high porosity, such as electrospinning, thus putting all the premises for cellular repopulation and antimicrobial protection. Abstract : Au/Ag core/shell nanorods are a synergistic bimetallic system for integration in chitosan‐based scaffolds that bind to connective tissue upon optical irradiation, change in color according to the environmental level of oxidative stress, hold a reservoir of antimicrobial Ag cations, and retain their compatibility with fabrication processes as electrospinning, which have made this polysaccharide so attractive in tissue engineering.